Geister in Kambodscha Existenz, Macht und rituelle Praxis - Christensen, Paul (Universitätsverlag Göttingen, 2020)
In this dissertation, Paul Christensen examines the significant roles played by spirits in Cambodian society. In particular, he focuses on the handling of the traumatic past, the religious identification of Cambodians, the political empowerment of elites through spiritual legitimation strategies, and the living ritual practice of spirit mediums in Cambodia. Based on 13 months of ethnographic field research and an innovative methodology utilizing actor-network theory, the research provides an emic understanding of these religious phenomena in terms of a '(re-)enchanted modernity' that is manifesting itself across Southeast Asia. The dissertation makes a seminal contribution to the scholarly understanding of spirits. It is compelling not only because of the novel connections provided by its methodology; its ethnographic descriptions of social topics such as power, existence, religion, healing, love or mourning provide new insights into religious life in a rapidly changing country.